Gender still determines how, and how long, we work - Wiebke Schmitz (Rapporter från Åldrande och social förändring, 2023)
Female-coded family work keeps women away from late working life – but it makes a difference where in Europe they live because Nordic countries do not recognize this divide. Key Findings Childcare impacts upon late working life – women tend to be employed part time or outside paid labor if they engaged in childcare during earlier life stages; men with children are more likely to be in full-time employment. Women are more affected by early working life decisions – previous labor-market participation or a reduction in working hours due to childcare obligations have a greater impact on late working life. A North–South divide in Europe – it is mostly in southern and western Europe that women’s domestic work or part-time employment prevents full-time employment in late working life, but in northern Europe, female employment in late working life is barely affected by previous family obligations. This research on gendered late-working-life trajectories is part of the research programme EIWO. Schmitz, W., Naegele, L., Frerichs, F., & Ellwardt, L. (2023): Gendered late working life trajectories, family history and welfare regimes: Evidence from SHARELIFE. European Journal of Ageing, 20, 5. https://doi.org/10.1007/s10433-023-00752-3 (open access). The paper received the "Best Paper Award 2023 for Early Career Researchers" from the German Gerontological Association (see https://www.dggg-online.de/best-paper-award.html).